2004
DOI: 10.1590/s1516-89132004000500003
|View full text |Cite
|
Sign up to set email alerts
|

Partition of proteins in aqueous two-phase systems based on Cashew-nut tree gum and poly(ethylene glycol)

Abstract: The partitioning of two proteins, bovine serum albumin (BSA) and trypsin was studied in an aqueous poly(ethylene glycol)(PEG)- Cashew-nut tree gum system. The phase diagram was provided for Cashew-nut tree gum and PEG molecular weight of 1500 at two different temperatures. The influence of several parameters including concentrations of polymers, pH, salt addition and temperature on the partitioning of these proteins were investigated.. The results of this research demonstrated the importance of the protein cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…Some authors have reported an increase in the K e with temperature; Sarubbo et al [32] observed an increase in K (trypsin) when using an aqueous two-phase system comprising 13% PEG 1,500 and 21% cashew-nut tree gum as temperature increased from 25 to 40 • C. Other reports have demonstrated that the K e decreases or does not have any temperature dependence; Souza et al [6] noted a decrease in K e for porcine pancreatic lipase using 20% PEG 8000 g/mol and 18% potassium phosphate.…”
Section: Influence Of Temperaturementioning
confidence: 98%
“…Some authors have reported an increase in the K e with temperature; Sarubbo et al [32] observed an increase in K (trypsin) when using an aqueous two-phase system comprising 13% PEG 1,500 and 21% cashew-nut tree gum as temperature increased from 25 to 40 • C. Other reports have demonstrated that the K e decreases or does not have any temperature dependence; Souza et al [6] noted a decrease in K e for porcine pancreatic lipase using 20% PEG 8000 g/mol and 18% potassium phosphate.…”
Section: Influence Of Temperaturementioning
confidence: 98%
“…Furthermore, K increases with increase in TLL. As the PEG-PAA composition increases, the number of polymer units involved in the bio-molecular partitioning also increases resulting in more protein molecules partitioning into the PEG phase due to hydrophobic interaction between the protein and PEG [29,43].…”
Section: Effect Of Peg Molecular Weight On the Protein Partitioning Imentioning
confidence: 99%
“…Sodium chloride of different concentrations (0-1 M) was used for the protein partitioning in PEG-PAA system. The selection of NaCl is based on the reports that NaCl favors the protein transfer to the top phase (PEG rich) of the two-phase system [43]. Effect of NaCl addition on partition coefficients of protein in PEG-PAA systems at optimum condition with different NaCl concentrations are shown in Fig.…”
Section: Effect Of Nacl On Protein Partitioning In Peg-paa Systemmentioning
confidence: 99%
“…The former is expensive, the medium is highly viscous and the process is hard to validate when crude dextran fractions are used so the latter is preferred especially for large-scale operation, as long as the enzyme withstands the high ionic strength required in the salt phase (Gupta et al 1999;Banik et al 2003). Several other biphasic systems have been tried with the purpose of using less expensive an more environmentally benign polymers (Tjerneld et al 1986;Andersson and Hahn-Hagerdal 1990;Miranda and Berglund 1990;Kepka et al 2003;Raghavarao et al 2003;Sarubbo et al 2004;Rosso et al 2005;Bezerra et al 2006), but the polyethyleneglycol-salt system is still the most used (Sarmento et al 1997;Iwamoto and Shiraiwa 2005;Dolia and Gaikar 2006;Jaw et al 2007). Two-phase partitioning can be smoothly integrated to the extraction step (Zhou et al 1997;Su and Feng 1999;Chang and Su 2005) and can also be improved by combining with affinity ligation (affinity partition) Lam et al 2004;Teotia and Gupta 2004;Castell et al 2006).…”
Section: Removal Of Cell Debrismentioning
confidence: 99%